Issues and principles on non-navigational use of international watercourses - Alsaadi, Saad Abbas Kadhim; Rasyikah Md. Khalid,; Wan Siti Adibah Wan Dahalan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The concept of international watercourse has been used in many international conventions referring to a river and its tributaries and related canals crossing two or more countries. The notable ones include the Mekong River which crosses five states in the East Asia region and the Danube and Rhine rivers which cross 12 states in Europe. This article addresses relevant international principle which will justify the claims and counter-claims on non-navigational use of international watercourses. It justifies the conflicting parties’ demands on shared watercourses. Accordingly, this paper adopts the qualitative doctrinal analysis of the principle of reasonable and equitable utilization under the United Nations Convention on the International Watercourses (UNWC) 1997. Relevant provision will be analysed and harnessed in addressing the respective conflict and weighing each argument of the conflicting parties. It is hoped that the utilisation of the available legal recourses will help strengthen the exisitng legal framework in solving conflict over non-navigational use of international watercourses.